Sacred Modernity : Nature, Environment and the Postcolonial Geographies of Sri Lankan Nationhood. - Jazeel, Tariq (Liverpool : Liverpool University Press, 2013)
This book explores the relationships between nature and environment and the contested politics of nationhood in contemporary Sri Lanka.
7 Over-determinations: Architecture, Text, PoliticsConclusion: Sri Lankan Nature as Problem Space; Bibliography; Index.
Print version record.
Includes bibliographical references and index.
Keywords: Nationalism -- Sri Lanka; Nature and civilization -- Sri Lanka; Nature -- Social aspects -- Sri Lanka; SOCIAL SCIENCE -- Human Geography; Nationalism; Nature and civilization; Nature -- Social aspects; Sri Lanka; Nationalism; Nature and civilization; Nature -- Social aspects; Nationalbewusstsein; Natur; Sri Lanka; Sri Lanka; Electronic books; Electronic book